2021
DOI: 10.1186/s13765-021-00667-6
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic effect of Lactococcus lactis subsp. cremoris RPG-HL-0136 on intestinal mucosal immunity in mice

Abstract: Lactococcus lactis subsp. cremoris is a lactic acid bacterium commonly used in the cheese manufacturing industry. It is known to produce antibacterial peptides and has recently received attention for its role as a probiotic strain. Here, we report the isolation of a new strain, Lactococcus lactis subsp. cremoris RPG-HL-0136 (RPG0136) from dried compost, which exhibits strong antibacterial activity. When RPG0136 was fed to mice, it increased the intestinal population of two beneficial bacteria, Lactobacillus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The difference between our study and the previous study was the health status of the participants. In another study using a healthy mouse model, no changes in immunogenicity were observed when L. lactis was administered, which is consistent with the results of this study [ 47 ]. On the other hand, in a previous study with 8 weeks of probiotic administration, IFN-γ increased significantly compared to that at predose [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…The difference between our study and the previous study was the health status of the participants. In another study using a healthy mouse model, no changes in immunogenicity were observed when L. lactis was administered, which is consistent with the results of this study [ 47 ]. On the other hand, in a previous study with 8 weeks of probiotic administration, IFN-γ increased significantly compared to that at predose [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the W3 sample, where microalgal biomass was used without sugar, especially the L. nagelii probiotic showed a better development, which can be concluded that the prebiotic released by L. nagelii was more secreted in this kefir sample (W3), thus the potential synergistic relationship was higher. Another species that strikes attention with its probiotic role and known for its antibacterial peptides production, Lactococcus cremoris , was slightly found in the control kefir sample; however, it showed an increase in kefir samples fortified with microalgal biomass (Park et al ., 2021). Furthermore, probiotic species Lactococcus lactis had a high relative abundance in W2 (20.034%), W1 (13.8%), and W3 (9.181%) samples, and its abundance showed a significant ( P < 0.05) change in W (1.52%) and W4 (0.77%) samples (Kiani et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Butyric acid production was seemingly related to Streptococcus, Lactococcus, Weissella, and Leuconostoc. These bacteria can produce other organic acids, such as acetic and butyric acids, from organic matter and also perform lactic acid fermentation in certain niches [52][53][54]. As shown in Figure 6a, on day In addition, the composition of VFAs varied among the groups with different amino acids.…”
Section: Microbial Community Analysismentioning
confidence: 98%